Community Based Tourism (CBT) Planning- A Mechanism for Socio-Ecology Survival: A Case Study of Lake Urmia IRAN - Fathi, Tohid (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The current study aims to assess the benefits and advantages of developing CBT in Lake Urmia region. Although Lake Urmia and the settlements around the Lack have various tourism potentials such as natural, cultural and historical tourism attractions, this area still remained un-known for tourists, and the settlements around the Lack suffer from unemployment and poverty. On the other hand, due to lake of water for irrigation, agriculture situation in the area is deteriorating and the current situation has forced communities around the lake to leave their settlements. While, improving tourism industry in the region and involving communities in tourism activities can be a suitable alternative and supplement for agriculture. Unfortunately, Lake Urmia has suffered decline due to mismanagement of water resources that fed the lake. Once the world’s sixth largest saltwater lake, Lake Urmia, lost in the desolate mountains of north-western Iran, has begun shrinking. As the lake has dried up and its shores have started to recede, the surrounding land has begun to die, causing an unprecedented ecological disaster. Located near the Turkish border between the provinces of East Azerbaijan and West Azerbaijan, Lake Urmia has been vanishing for three decades. This study is an attempt to provide an investigation into the surrounding communities and come up with possible solution to the dire situation. The transformation of the lake and its environment can be translated to advantages for CBT. The remaining of the lake with its new features has the potential for tourism and especially for nature-based tourism. For the purpose of this study, a qualitative research will be applied to explore and understand the concerns of the surrounding communities for involvement in CBT. Because without understanding the community’s views, it will not be possible to strategize the processes of CBT. Convenience sampling and in-depth interview with the local communities will be furnished. The tourism industry in Iran has very high potential for growth and development. According to the World Tourism Organization, Iran ranked tenth of the ancient and historical attractions and ranked fifth in the world's natural attractions. According to experts the industry does not enjoy the development that it deserves. The reason for this is the lack of adequate and scientific investigation towards policy making process. Knowing the fact, community involvement is fundamental to the successful of alternative tourism ventures. Community-Based Tourism is one of the ways to develop tourism in communities that are faced with transiting to a new economy. The CBT that is envisaged in this study must consider the ecological integrity of whatever is left from the previous ecosystem. It is also said that this type of tourism can preserve and strengthen the culture, heritage and traditions of the local community. Another goal is to protect the natural heritage of the indigenous community. Keywords: Community-based tourism (CBT), Alternative tourism, Community participation, Socio-ecological integrity, Lake Urmia

ÖZ: Mevcut çalışma, Urmia Gölü bölgesinde TDT'nin (Topluma Dayalı Turizm) gelişmesinin yararlarını ve yararlarını değerlendirmeyi amaçlamaktadır. Urmia Gölü ve çevresindeki yerleşimlerin doğal, kültürel ve tarihi turizm cazibeleri gibi çeşitli turizm potansiyelleri bulunmakla birlikte, bu alan hala turistler tarafından bilinmemektedir ve çevresindeki yerleşim birimleri işsizlik ve yoksulluk yüzünden acı çekmektedir. Öte yandan, tarım durumu kötüleşmekte ve mevcut durum göl çevresindeki toplulukların yerleşim yerlerini terk etmesine neden olmuştur. Bölgede turizm endüstrisinin geliştirilmesi ve toplulukların turizm faaliyetlerine dahil edilmesi tarım için uygun bir alternatif ve ilave olabilir. Maalesef, Urmia Gölü, gölü besleyen su kaynaklarının yanlış yönetilmesi nedeniyle düşüş gösterdi. Dünyanın en büyük altıncı tuzlu su gölü olan Urmia, kuzey batı İran'ın ıssız dağlarında kaybolmaya başlamıştı. Gölün kuruması ve kıyıları gerilemeye başlayınca çevredeki topraklar ölmeye başlıyor ve benzeri görülmemiş bir ekolojik felaket yaratıyor. Doğu Azerbaycan ve Batı Azerbaycan arasındaki Türk sınırının yakınında bulunan Urmiye Göleti, 30 yıl boyunca yok oluyor. Bu çalışma çevredeki topluluklar hakkında bir araştırma yapmak ve korkunç duruma olası bir çözüm bulmak için yapılan bir girişimdir. Gölün dönüşümü ve çevresi TDT için avantajlara dönüştürülebilir. Gölün yeni özellikleri ile geri kalan kısmı turizm potansiyeline ve özellikle doğa tabanlı turizm potansiyeline sahiptir. Bu çalışmanın amacı, TDT'ye katılmak için çevredeki toplumların endişelerini keşfetmek ve anlamak için niteliksel bir araştırma uygulanacaktır. Çünkü topluluğun görüşlerini anlamaksızın, TDT süreçlerini strateji oluşturmak mümkün olmayacaktır. Kolaylık örneklemesi ve yerel topluluklarla derinlemesine röportaj yapılacaktır. İran'daki turizm endüstrisinin büyüme ve gelişme potansiyeli çok yüksek. Dünya Turizm Örgütü'ne göre, İran, eski ve tarihi mekanların onda birini ve dünyanın doğal cazibeleri arasinda beşinci sırada yer aldı. Uzmanlara göre, endüstri, hak ettiği gelişime sahip değildir. Bunun nedeni, politika oluşturma sürecine yönelik yeterli ve bilimsel soruşturmanın bulunmamasıdır. Aslında, topluluğun katılımı, alternatif turizm girişimlerinin başarılı olması için temel önemdedir. Topluma Dayalı Turizm, topluluklarda yeni bir ekonomiye geçişle karşı karşıya olan turizmin geliştirilmesinin yollarından biridir. Bu çalışmada öngörülen TDT, önceki ekosistemin geriye kalanının ekolojik bütünlüğünü göz önüne almalıdır. Ayrıca, bu tür turizmin yerel topluluğun kültür mirasını ve geleneklerini koruyabileceği ve güçlendireceği söyleniyor. Bir başka amaç, yerli halkın doğal mirasını korumaktır. Anahtar Kelimeler: Toplum temelli turizm (TDT), Alternatif turizm, Topluluk katılımı, Sosyo-ekolojik bütünlük, Urmiye Gölü
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2018. Supervisor: Prof. Dr. Habib Alipour.
Keywords: Tourism; Tourism--Iran; Community-based tourism (CBT); Alternative tourism; Community participation; Socio-ecological integrity; Lake Urmia